2009
DOI: 10.1111/j.1744-7348.2009.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitric oxide stimulates plant growth and improves the quality of spinach (Spinacia oleracea)

Abstract: Nitric oxide (NO) is an endogenous signalling molecule implicated in a growing number of plant processes and has been recognised as a plant hormone. The present research employed spinach plant (Spinacia oleracea cv. Huangjia) and closed growth chambers to investigate the effects of gaseous NO application on vegetable production in greenhouses. Treatment of low concentration of NO gas (ambient atmosphere with 200 nL L 21 NO gas) significantly increased the shoot biomass of the soil-cultivated plants as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
(37 reference statements)
4
18
0
Order By: Relevance
“…Carotene, ascorbic acid, glutathione, flavonoids and polyphenol serve as good oxidant scavengers, and these compounds are often used to assess antioxidant status and hence act as a parameter for vegetable quality . Here we observed that the carotene concentrations in the edible part of spinach plants from 6‐day NO 3 − ‐free treatments were lower than those from NO 3 − ‐containing treatments, indicating that the presence of NO 3 − in SANSPH should be a critical factor in maintaining the carotene level in plants.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Carotene, ascorbic acid, glutathione, flavonoids and polyphenol serve as good oxidant scavengers, and these compounds are often used to assess antioxidant status and hence act as a parameter for vegetable quality . Here we observed that the carotene concentrations in the edible part of spinach plants from 6‐day NO 3 − ‐free treatments were lower than those from NO 3 − ‐containing treatments, indicating that the presence of NO 3 − in SANSPH should be a critical factor in maintaining the carotene level in plants.…”
Section: Discussionmentioning
confidence: 62%
“…Carotene, ascorbic acid, glutathione, flavonoids and polyphenol serve as good oxidant scavengers, 20,27 -29 and these compounds are often used to assess antioxidant status and hence act as a parameter for vegetable quality. 20,30 Here we observed that the carotene concentrations in the edible part of spinach plants from 6-day NO 3 − -free treatments were lower than those from NO 3 − -containing treatments, indicating that the presence of NO 3 − in SANSPH should be a critical factor in maintaining the carotene level in plants. However, both ascorbic acid and glutathione concentrations were increased with the elevation of NH 4 + concentration in the growth medium ( Table 3), indicating that NH 4 + facilitates the production of these compounds in plants.…”
Section: Proper Short-term Alteration Of Nitrogen Supply Prior To Harmentioning
confidence: 67%
“…It can regulate plant growth in a dose-dependent fashion, with low concentrations promoting and high concentrations inhibiting growth (Anderson and Mansfield 1979;Hufton et al 1996;Leshem and Haramaty 1996;Gouvea et al 1997;Prado et al 2004;Lehner et al 2009;Jin et al 2009). In roots, NO stimulates tip growth and promotes root hair initiation (Yemets et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Nitric oxide acts as an antioxidant molecule and plays a protective role against stress (Beligni and Lamattina, 1999a) in a dose-dependent manner, the best being a concentration of 10 −5 M. The NR activity was stimulated by NO, possibly induced by a posttranslational regulatory pathway (Jin et al, 2009). The NR activity is enhanced by napthalene acetic acid (NAA) (an analogue of indole acetic acid (IAA)) in chicory (Cichorium intybus L.; Vuylsteker et al, 1998), by cytokinin benzyladenine in Arabidopsis (Yu et al, 2001), and by salicylic acid in maize (Zea mays L.; Jain and Srivastava, 1981).…”
Section: Discussionmentioning
confidence: 99%